Development and differentiation : the case of TILCOR/ARDA irrigation activities in Sanyati (Zimbabwe), 1939 to 2000 - Phimister, I.R. (Ian R.) (University of Pretoria, 2013)
Thesis (PhD (History))--University of Pretoria, 2008.